2017
DOI: 10.1530/rep-16-0591
|View full text |Cite
|
Sign up to set email alerts
|

SRC family kinases in hamster spermatozoa: evidence for the presence of LCK

Abstract: Sperm capacitation is a prerequisite for successful fertilization. Increase in tyrosine phosphorylation is considered the hallmark of capacitation and attempts to understand its regulation are ongoing. In this regard, we attempted to study the role of SRC family kinases (SFKs) in the hamster sperm functions. Interestingly, we found the presence of the lymphocyte-specific protein tyrosine kinase, LCK, in mammalian spermatozoa and further characterized it in terms of its localization and function. LCK was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
2
2
0
Order By: Relevance
“…p-SFK-Y416 was present in patch-like patterns over the sperm head, including the acrosomal region, which differed from the c-Src only enriched in the sperm head except for acrosomal region. This suggests that the primary SFK being phosphorylated is not c-Src, which is consistent with previous results showing a species-specific preference of phosphorylated SFK members in mammalian sperm [24]. Further research is required to identify the SFKs in chicken sperm.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…p-SFK-Y416 was present in patch-like patterns over the sperm head, including the acrosomal region, which differed from the c-Src only enriched in the sperm head except for acrosomal region. This suggests that the primary SFK being phosphorylated is not c-Src, which is consistent with previous results showing a species-specific preference of phosphorylated SFK members in mammalian sperm [24]. Further research is required to identify the SFKs in chicken sperm.…”
supporting
confidence: 90%
“…The presence of SFKs have been reported in the sperm of a few species [24,25]. Our immunoblotting analysis showed the presence of c-Src, a prototypic member of SFK, in addition to p-SFK-Y416, in chicken sperm.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Tubular epithelial cells (TECs) play an important role in renal diseases, especially in tubulointerstitial inflammation and fibrosis, which is a pathological process involved in a variety of cytokines and inflammatory mediators. Lymphocyte-specific protein-tyrosine kinase ( LCK ) and a SRC family protein-tyrosine kinase are located in the cytoplasm of TECs and form the key signal transduction molecule in the process of intracellular signal transduction (Singh et al, 2017). Li et al have investigated the effect of the LCK pathway activation on the IL-12 signal transduction of TECs and found that LCK may regulate the LCK c-Jun signaling pathways in TEC, while the inflammation of TEC mediated by the activation of the LCK pathway is related to the expression of c-Jun promoted by IL-12 (Li et al, 2001).…”
Section: Discussionmentioning
confidence: 99%